EFEKTIVITAS MODEL PEMBELAJARAN KONTEKSTUAL DALAM PEMBELAJARAN MATERI BIOTEKNOLOGI DI SMA NEGERI CIANJUR - Asep Suhendi Aripin (LPPM UNSAP & FISIP UNSAP, 2016)
This study examines the effectiveness of learning CTL (Contextual Teaching and Learning) on the matter of biotechnology, namely making nata de coco. The method used is the method of quasi-experimental research subjects students take one SMAN in Cianjur. The study used a descriptive analytic techniques. The effectiveness of learning is determined based on the following criteria: 1) the significance of the thoroughness of learning outcomes, in terms of mastery of concepts is achieved; 2) the ability of inquiry indicated during PBM; 3) interaction pattern formed during PBM, namely the interaction patterns are symmetrical, asymmetrical shifting, and asymmetrical, adapted from Johnson & Johnson (1975). From these results it is found that it turns learning model is effective with the fact that support, namely: 1) The study results turned out to be significantly better than the complete learning criteria (Zscore = 5.69); 2) the ability of scientific inquiry at all emerges with the ability greatest scientific investigations (24.45%) and the lowest in the ability to develop descriptions, explanations, predictions and models based on evidence (10.70%); 3) interaction pattern formed is symmetrical patterns of interaction (50.72%) and the shifting asymmetric (49.36).